Pineapple quality in a traditional cultivation system in different soil classes - Ramos, Michele Ribeiro; Freire, Talita Maia; dos Santos, Francisca Marta Barbosa; Uhlmann, Alexandre; dos Santos, Danilo Marcelo Aires; Campos, Lorena dos Santos (Comunicata Scientiae, 2020)
Pineapple (Ananas comosus (L.) Merril) is considered one of the most important fruits of the tropical and subtropical regions, and the third most-produced in the world due to its high commercial expansion in the world market, in recent years. Therefore, this work aimed to evaluate the influence of landscape position on pineapple quality. The work was developed at the Providência Farm, located in the municipality of Miracema do Tocantins. The following soil parameters were evaluated: hydraulic conductivity - KS, soil bulk density – DS, and total porosity – TP, as well as the following quality attributes: titratable acidity - TA, length and diameter of infructescences, total fresh mass - TM, fresh mass of infructescences – IM, and soluble solids – SS. The analyses were performed at the Agri-Environmental Laboratory of the Agricultural Sciences Complex of the Federal University of Tocantins. Less massive infructescences developed on more porous soils. The variation in the mass of infructescences is not associated with soil types, but rather with soil porosity. Soils with higher KS tend to increase the chances of producing infructescences with high acidity and high levels of soluble solids. The DS did not result in a significant association with the pineapple quality attributes. The infructescences were not affected by the landscape position. No position in the landscape influenced fruit quality. In general, the infructescences showed low acidity and low levels of soluble solids, with length and diameter of infructescences below the standard of the cultivar ‘Pérola’.